Analysis of risk stratification and prevention of sudden death in pediatric patients with hypertrophic cardiomyopathy: Dilemmas and clarity - Bonaventura, Jiri; Maron, Barry J; Berul, Charles I; Rowin, Ethan J; Maron, Martin S (Heart rhythm O2, 2023)
Hypertrophic cardiomyopathy (HCM) has been considered the most common cause of sudden death (SD) in the young. However, introduction of implantable cardioverter-defibrillators (ICDs) in HCM has proved highly effective and the mainstay of preventing SD in children, adolescents, and adults by terminating malignant ventricular tachyarrhythmias. Nevertheless, ICD decision making is generally regarded as more difficult in pediatrics, and the strategy for selecting ICD patients from this population remains without consensus. Prospective studies in HCM children and adolescents have shown the American Heart Association/American College of Cardiology traditional major risk marker strategy to be reliable with >90% sensitivity in selecting patients for SD prevention. International data in >2000 young HCM patients assembled over 20 years who were stratified by major risk markers showed ICDs effectively prevented SD in 20%. Alternatively, novel quantitative risk scoring initiatives provide 5-year risk estimates that are potentially useful as adjunctive tools to facilitate discussion of prophylactic ICD risks vs benefit but are as yet unsupported by prospective outcome studies. Risk scoring strategies are characterized by reasonable discriminatory statistical power (C-statistic 0.69-0.76) for identifying patients with SD events but with relatively low sensitivity, albeit with specificity comparable with the risk marker strategy. While some reticence for obligating healthy-appearing young patients to lifelong device implants is understandable, underutilization of the ICD in high-risk children and adolescents can represent a lost opportunity for fulfilling the long-standing aspiration of SD prevention. This review provides a critical assessment of the current strengths and weaknesses of SD risk stratification strategies in young HCM patients in an effort to clarify clinical decision making in this challenging subpopulation.
Keywords: Implantable cardioverter-defibrillators; Hypertrophic cardiomyopathy; Sudden death; Decision making; Pediatric; Ventricular arrhythmias